An Analysis of Impoliteness Strategies in â€œCan You Ever Forgive Me?â€ Movie - Kelvin Kelvin; Gaguk Rudianto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study applied pragmatics study to analyze impoliteness strategies that based on the movie titled â€œCan You Ever Forgive Me?â€ directed by Marielle Heller. The aim of this study was to discover the strategies of impoliteness that occurred from the conversation in the movie. The utterances were found and gathered by applying the theory of Culpeper (1996) for the data source. The object of this research was impoliteness strategies. The data source contained the conversation that was uttered by the characters from the movie â€œCan You Ever Forgive Me?â€. The descriptive qualitative research design was employed to obtain the research findings. The data were acquired in a non-participatory method, which means that no participants were required during the process of data collection. The results revealed that the movie utilized all impoliteness strategies. It was found that bald-on-record impoliteness had five utterances, positive impoliteness had four, negative impoliteness had three, sarcasm/mock impoliteness contained two, and withhold politeness had only one.